2020
DOI: 10.1039/c9rp00198k
|View full text |Cite
|
Sign up to set email alerts
|

Building mental models of a reaction mechanism: the influence of static and animated representations, prior knowledge, and spatial ability

Abstract: In chemistry, novices and experts use mental models to simulate and reason about sub-microscopic processes. Animations are thus important tools for learning in chemistry to convey reaction dynamics and molecular motion. While there are many animations available and studies showing the benefit of learning from animations, there are also limitations to their design and effectiveness. Moreover, there are few experimental studies into learning chemistry from animations, especially organic reaction mechanisms. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 51 publications
0
33
0
1
Order By: Relevance
“…While they may be able to show users the process of chemical reactions, the lack of user interactivity takes away a crucial aspect of teaching; that is, students would not be able to visualize changes to these models arising from reaction mechanisms . Such cognitive skill is crucial to the understanding of chemistry as a subject …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While they may be able to show users the process of chemical reactions, the lack of user interactivity takes away a crucial aspect of teaching; that is, students would not be able to visualize changes to these models arising from reaction mechanisms . Such cognitive skill is crucial to the understanding of chemistry as a subject …”
Section: Introductionmentioning
confidence: 99%
“…30 Such cognitive skill is crucial to the understanding of chemistry as a subject. 31 Learning Nucleophilic Addition in CM1121: Organic Chemistry I This project NuPOV ("Nucleophile's Point of View") aimed to utilize AR technology to assist in teaching chemistry concepts to students at the university level. NuPOV was piloted in the freshman course Organic Chemistry I (course code CM1121).…”
Section: ■ Introductionmentioning
confidence: 99%
“…15,16 Recent studies have shown that the use of animations help students to move to a more dynamic, and expert, view of reactions. 17 The Mechanisms app by Alchemie ("the App") was developed as a touch-screen software interface to enable students to make sense of the EPF of organic chemistry through experimentation. 18 In the App, students investigate reactions by moving electrons to make and break bonds, to which the App responds immediately using graphical and audio feedback.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The question becomes how best to help students understand the EPF reasoning of organic chemistry and move beyond memorizing a procedure to explaining a process. Research has shown that novice learners in organic chemistry focus on surface features when presented with an organic reaction, while experts “see” deeper concepts during each step of a mechanistic pathway. , Recent studies have shown that the use of animations help students to move to a more dynamic, and expert, view of reactions . The Mechanisms app by Alchemie (“the App”) was developed as a touch-screen software interface to enable students to make sense of the EPF of organic chemistry through experimentation .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Recent studies have shown that the use of animations help students to move to a this more dynamic, and expert view, of reactions. 17 The Mechanisms app, by Alchemie, was developed to allow students to experiment and "play" with the electrons and bonds of organic chemistry to make sense of the EPF in a game-like experience. 4,18 The original hypothesis that grounded the app's development was inspired by Jerome Bruner's theory of constructivism, and that if students could interact with and get immediate feedback from a software system that presented EPF on a touchscreen, they would be more likely to reason through the mechanisms of organic chemistry.…”
Section: Introductionmentioning
confidence: 99%